The Impact of Covid-19 on Online Teaching and Learning (TnL) Towards Teachers in Malaysia - Shahrina Ismail; Mohammad Ilham Husaini Mohammad Nazeri; Sharifah Fairuz Syed Mohamad (USIM Press, 2024)
teachers; impact; effectiveness; challenges; school reopening